Validity of the X-factor computation methods and relationship between the X-factor parameters and clubhead velocity in skilled golfers - Kwon, Y. H.; Han, K. H.; Como, C.; Lee, S.; Singhal, K. (Sports Biomechanics, 2013)
The purpose of this study was to assess the validity of the X-factor computation methods and to examine whether direct relationships exist between the X-factor parameters and the clubhead velocity in a group of skilled male golfers (n = 18, handicap = - 0.6 ± 2.1). Five driver trials were captured from each golfer using an optical motion capture system (250 Hz). Two plane-based methods (conventional vs. functional swing plane-based) and one Cardan rotation-based method (relative orientation) were used to compute select X-factor (end of pelvis rotation, top of backswing, ball impact (BI), and maximum), X-factor stretch (stretch and maximum stretch), and X-factor velocity (BI and maximum) parameters. The maximum clubhead velocity was extracted and normalized to golfer's body height to eliminate the effect of body size. A one-way repeated MANOVA revealed that the computation methods generated significantly different X-factor parameter values (p < 0.001). The conventional method provided substantially larger X-factor values than the other methods in the untwisting phase and the meaningfulness of select X-factor parameters generated by this method was deemed questionable. The correlation analysis revealed that the X-factor parameters were not directly related to the maximum clubhead velocity (both unnormalized and normalized).